Chapter Słowacki e l'idea di evoluzione: per una rivisitazione di Genezis z Ducha - Caldarelli, Raffaele (Biblioteca di Studi Slavistici, 2019)
This article analyzes Juliusz Słowacki's Genezis z Ducha in terms of Romantic idealism and early attempts at biological thought. We examine Słowacki's ideas on life and the universe within the context of Western science's long quest for existential meaning, comparing them with the thought and ideas of various 20th-century thinkers, including Pierre Teilhard de Chardin.